Rapid exome sequencing and adjunct RNA studies confirm the pathogenicity of a novel homozygous ASNS splicing variant in a critically ill neonate. Issue 11 (9th September 2020) - Akesson, Lauren S.; Bournazos, Adam; Fennell, Andrew; Krzesinski, Emma I.; Tan, Kenneth; Springer, Amanda; Rose, Katherine; Goranitis, Ilias; Francis, David; Lee, Crystle; Faiz, Fathimath; Davis, Mark R.; et al.
Abstract: Rapid genomic diagnosis programs are transforming rare disease diagnosis in acute pediatrics. A ventilated newborn with cerebellar hypoplasia underwent rapid exome sequencing (75 h), identifying a novel homozygous ASNS splice‐site variant (NM_133436.3:c.1476+1G>A) of uncertain significance. Rapid ASNS splicing studies using blood‐derived messenger RNA from the family trio confirmed a consistent pattern of abnormal splicing induced by the variant (cryptic 5′ splice‐site or exon 12 skipping) with absence of normal ASNS splicing in the proband. Splicing studies reported within 10 days led to reclassification of c.1476+1G>A as pathogenic at age 27 days. Intensive care was redirected toward palliation. Cost analyses for the neonate and his undiagnosed, similarly affected deceased sibling, demonstrate that early diagnosis reduced hospitalization costs by AU100, 828. We highlight the diagnostic benefits of adjunct RNA testing to confirm the pathogenicity of splicing variants identified via rapid genomic testing pipelines for precision and preventative medicine. Abstract : We present rapid RNA studies that diagnosed a seriously ill newborn with asparagine synthetase deficiency after a homozygous ASNS splicing variant was detected by ultra‐rapid exome sequencing.